Heterogeneity in migration network effects across cultures - Tamara Bogatzki (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
I empirically assess the importance of socially interdependent origin cultures as opposed to socially independent ones for network effects in inter-national migration. I propose that societies that emphasise collectivist behaviour accumulate larger levels of communityspecific social capital than individualist societies. Furthermore, while community-specific social capital makes migration away from the group costly it can be recovered by entering a corresponding network abroad. My estimates show consistent positive effects of social interdependence on the importance of migrant diasporas for bilateral emigration rates from all over the world to 30 OECD destinations across a plethora of specifications. For people from an origin with maximal emphasis on collectivism the network effect can be up to more than twice as large as for people from the individualist pole of the scale. The pattern is reflected when comparing trust in other people across different degrees of generalisation, suggesting that the heterogeneous diaspora effect may indeed be driven by higher ingroup-specific social capital in collectivist cultures. – – Kollektivistische Gesellschaften verfügen über ein höheres gemeinschaftsspezifisches Sozialkapital als individualistische Gesellschaften. Dieses gesellschaftsspezifische Sozialkapital macht das Verlassen der Gemeinschaft kostspieliger, kann jedoch anteilig zurückgewonnen werden, wenn Individuen in Zielländer mit entsprechenden Diasporen migrieren. Die Forschungsarbeit zeigt, dass eine höhere gegenseitige soziale Abhängigkeit im Herkunftsland die Wichtigkeit von Netzwerken für die Selektion in 30 OECD Zielländer signifikant steigert. Der Effekt ist konsistent über verschiedene empirische Spezifikationen hinweg. Für Migrant*innen aus kollektivistischen Herkunftsländern ist der Netzwerkeffekt bis zu doppelt zu groß wie für Migrant*innen aus individualistischen Herkunftsländern. Ein vergleichbares Muster zeigt sich für allgemeines Vertrauen, das in kollektivistischeren Kulturen niedriger ist und den vorgeschlagenen Sozial-KapitalMechanismus stützt.
Keywords: F22; Z13; 300; International Migration; Cultural Economics; Economic Sociology; Collectivism; Individualism; Migration Networks; Social Capital; Internationale Migration; Kulturökonomik; Wirtschaftsökonomik; Kollektivismus; Individualismus; Migrationsnetzwerke; Sozialkapital